Molecular simulation for the effect of electric fields on the yield behaviour and cracking process of insulation paper - Wang, Youyuan; Fan, Peng; Tian, Miao; Chen, Bijun (Molecular simulation, 2015)
In operation, the insulation paper used for transformers is subject to electric stress. This paper may deteriorate as a result of the accumulation of mechanical stress and the polarisation of the electric field. The effect of electric fields on insulation paper is typically investigated through macroscopic tests; thus, the microscopic mechanism must be explored further. In this study, single- and multi-chain cellulose models were constructed to simulate the yield behaviour of cellulose under a strong electric field (10 10 V m − 1 ) through molecular dynamics. The cracking process of insulation paper was also examined according to density functional theory. Results indicated that both single- and multi-chain celluloses yield under a strong electric field. This yield behaviour is consistent with that of the electric field, and it eventually breaks the cellulose chains. The energy gap between the lowest unoccupied and the highest occupied molecular orbitals suggested that cellulose molecules may encounter insulation breakdown at an electric field strength of 10 5 V m − 1 . Furthermore, the initial fracture in the molecular chain of cellulose was observed under the weakest glycosidic bond.